Public expenditure on agriculture and economic growth: a case study of Meghalaya - Dahun Shisha Dkhar; Utpal Kumar De (Agricultural Economics Research Review, 2023)
This paper assesses the impact of government expenditure on agriculture and allied activities on economic growth (GSDP) in Meghalaya during the period 1984-85 to 2013-14. We find a significant positive impact of agricultural expenditure on crop husbandry on GSDP growth. On the other hand, the impact of public expenditure on forestry, dairy and irrigation is found out to be negative. These findings conclude that although crop husbandry happens to have a significant positive impact of economic growth, the need for strengthening its linkages with other sectors cannot be undermined given the small and declining size of landholdings in the state.